Acinic cell carcinoma of ascending ramus mandible: a rare case report - Munjal, Manish; Rishi, Porshia; Tuli, Nitika; Singh, Harjinder; Talwar, Shivam; Sharma, Salony; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Acini cell carcinoma are low grade tumors of the salivary glands with a rare occurrence in the axial or appendicular skeleton. The parotid, submandibular and the minor salivary glands are sites of involvement in that order. Painless swelling is the usual presentation with a lytic appearance on radiology and imaging, CT or MRI, FNAC can to some extent differentiate between a benign or malignant lesion thereby dictating the likely extent of excision. On histopathological examination of resected specimens, acinic cell carcinoma shows tumor cells arranged as papillary clusters, acinar pattern and dispersed population with individual tumor cells displaying moderate nuclear pleomorphism, anisonucleosis, round nuclei and moderate amount of ill-defined granular cytoplasm. A unique intraosseous presentation of acinic cell carcinoma, in an elderly male, necessitated a segmental partial mandibulectomy and a comprehensive neck dissection. The tumour area was widely excised from the second premolar region to the coronoid process, and radical neck dissection was performed.